VALIDITY ANALYSIS OF STUDENT WORKSHEETS ON THE TOPIC OF HEAT TRANSFER CONDUCTION, CONVECTION AND RADIATION - Wifdatun Nisa; Noer Af'idah (NUKLEO SAINS : JURNAL PENDIDIKAN IPA, 2025)
Laboratories have an important role in science learning because by carrying out practicum activities, students get a direct learning experience in understanding the material being studied. The student worksheet (LKPD) developed in this study is a simple practicum activity that can be carried out even with inadequate laboratory facilities. The purpose of this study is to develop a student worksheet on conduction, convection and radiation heat transfer material for grade VII. This research method uses the Research and Development method with the ADDIE development model. The results of the validation assessment by experts showed a percentage of 90.90% and an average score of 360 with very feasible criteria.